Pipe Cleaner Flowers Pot - Yeny Novita Fitriani; Danendra Bramantyo; Mohammad Masrur Mauridhoh; Muhammad Yasin (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study aims to determine the influence of digital marketing and brand awareness on consumer purchase intention toward the Subeng Klasik product. A quantitative approach was employed using a questionnaire distributed to respondents. The data were analyzed using multiple linear regression. The results indicate that both digital marketing and brand awareness have a positive and significant effect on purchase intention when tested partially. However, brand awareness exerts a greater influence than digital marketing. Simultaneously, both variables also significantly and positively affect purchase intention. These findings imply that strengthening brand awareness strategies should be a primary focus in developing local product marketing such as Subeng Klasik.